Public Administration as a Scholarly Discipline Today–and How ICT Will Affect It - Drechsler, Wolfgang (Philippine Journal of Public Administration; Vol 61 No 1&2 (2017), 2019)
After sketching out how Public Administration (PA) scholarship looks today, this lecture asks how information and communication technology (ICT) will, or might, influence it in the near future. First, we look at what information and communication technology can already do today and how it has changed our life-world by 2017. Two critical, interlinked phenomena are then analyzed: MOOCs (massive open online courses) and their effects, and the current ability of algorithms to write a certain type of texts. These may have the effect to strongly enforce, even lock in, the current tendencies of PA, but they may also give rise to an altogether different kind of development of scholarly inquiry in the discipline and beyond.
Keywords: Public Administration, ICT, algorithms, MOOCs